Perencanaan Keuangan dan Pemasaran Bisnis Keluarga di Posyandu Lili RW 015 Komplek Pesona Pamulang Pondok Petir, Kota Tangerang Selatan - Diana Riyana H; Ifa Nurmasari; Novia Susanti (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2023)
It is undeniable that the Covid-19 pandemic has hampered the economy in Indonesia since almost two years ago. In 2020, most industries in Indonesia experienced a significant decline in sales. In addition, Indonesia is also projected to experience the slowest economic recovery process compared to other developing Asian countries. In this case, family businesses in Indonesia are also affected. For this reason, anticipatory steps are needed to secure the continuity of the family business which is part of the strength of MSMEs in Indonesia. The method used in this Community Service is to provide knowledge, share experiences and provide motivation on how to manage household finances and do family business marketing digitally. This activity is carried out while adhering to the Health protocol. The results of this Community Service activity show an increase in knowledge, insight, and motivation for housewives at the Pesona Pamulang Pondok Petir Complex, South Tangerang. Next there will be further cooperation in finance and marketing.